Mitochondrial uncoupling and glycolysis stimulation are beneficial for kinematics, functionality and oxidative homeostasis of cryopreserved ram sperm - Alves, Álvaro de Miranda; Losano, João Diego de Agostini; Leite, Roberta Ferreira; Rui, Bruno Rogério; Angrimani, Daniel de Souza Ramos; Hamilton, Thais Rose dos Santos [UNESP]; Mendes, Camilla Mota; Assumpção, Mayra Elena Ortiz D'Avila; Nichi, Marcilio (Elsevier, 2025)
The aim of the present study was to improve bioenergetics and oxidative status of cryopreserved ram sperm by uncoupling mitochondrial activity and stimulating glycolysis. To verify a potential synergism between mitochondrial uncoupling and glycolysis stimulation, as well as to determine the optimal concentrations of the respective treatments, the study was divided into two experiments. In Experiment 1, ejaculates from eight rams were diluted with the commercial extender (Botubov®), supplemented with the mitochondrial uncoupler CCCP (0, 1, 10, and 20 μM), with or without 5 mM glucose, and then subjected to cryopreservation. After thawing, sperm function and oxidative status analyses were conducted to determine the optimal CCCP concentration, which was selected for Experiment 2. In Experiment 2, ejaculates from seven rams were diluted with the commercial extender (Botubov®) and supplemented with CCCP at doses of 0, 2.5, 5, and 10 μM, with or without 5 mM glucose. After thawing, an analysis of sperm bioenergetics was performed. Differences between treatments were assessed using ANOVA, followed by LSD mean comparison test for the combination of factors. In both experiments, total and progressive motility were higher in the CCCP 10 μM + glucose 5 mM group. This same group exhibited less susceptibility to lipid peroxidation, lower DNA fragmentation (Experiment 1), and greater mitochondrial activity (Experiment 2). Furthermore, treatments with only CCCP were deleterious to sperm. In conclusion, the use of the mitochondrial uncoupler CCCP at a dose of 10 μM combined with 5 mM glucose was promising in improving post-thaw sperm attributes.
Keywords: Bioenergetics; Cryopreservation; Metabolism; Ovine; Oxidative stress; Semen